PENERAPAN PROSEDUR AUDIT ATAS PIUTANG ANGGOTA PADA KOPERASI KARYAWAN XYZ DI KANTOR AKUNTAN PUBLIK JEPTHA NASIB DAN JUNIHOL - Atika Widya Ningrum (2022)
The audit procedure is the stage carried out by the auditor in testing the financial position that has been prepared by the company's management. Receivables from cooperative members are claims originating from members of employee cooperatives arising from transactions on credit in the form of goods or services. In this employee cooperative, member receivables have a position on the balance sheet report. Accounts receivable from members is one of the accounts in the cooperative that has a material value and has a high risk of loss of receivables. Accounts receivable must be recorded and presented fairly and in accordance with accounting principles. Therefore, the KAP must carry out audit procedures and design them properly. The current client is an employee cooperative engaged in the construction sector. KAP JNJ in carrying out the implementation of audit procedures has been appropriate and the employee cooperative concluded that it has presented the financial statements fairly without exception.